DISTRIBUTION OF PLATINUM GROUP ELEMENTS AND RHENIUM BETWEEN METALLIC PHASES OF IRON METEORITES - Hirata T.; Nesbitt R.W. (My University, 1997)
In situ measurement of the platinum group elements (PGE) and Re by laser ablation-ICPMS allows fractionation patterns to be established between host (kamacite) and Ni-rich exsolved phases (taenite and plessite). Measurements on two IAB iron meteorites (Canyon Diablo and Odessa) show that, for the Ni-rich phases: (a) there is no significant fractionation for Ru and Rh; (b) Pd is enriched; and (c) Ir, Os and Pt are strongly depleted. We suggest that, in the case of kamacite, taenite and plessite, the controlling mechanism is ionic size with the order of ions (small to large) being Ir-Os-Pt-(Re)-Rh-Ru-Pd. This progression plots as a smooth curve on a diagram of relative abundance distribution vs. ionic size.A comparison of PGE and Re data on iron meteorites with published data from CI chondrites indicate that there is little or no relative fractionation between the elements. The exception is Re that is clearly enriched in kamacite relative to chondrites. This confirms earlier observations on the fractionation of Re/Os between bulk IAB irons and CI values.Metallic veins cutting graphite inclusions within the Canyon Diablo IAB meteorite are interpreted as a melt fraction from the iron meteorite. Abundance ratios for PGE and Re between kamacite and the metallic vein are similar to abundance ratios between kamacite and Ni-rich phases. The fact that those elements with large ionic radii (Rh, Ru and Pd) are concentrated in the metallic veins adds weight to the view that they represent a melt fraction.Our in situ measurements of the PGE and Re demonstrate that elemental fractionation takes place both during melt segregation and solid state diffusion (exsolution). The data have important implications for the Re/Os geochronometer and indicate that measurements of 187Os186Os ratios on individual phases within iron meteorites may provide a potential mineral isochron.
Keywords: PLATINUM GROUP; IRON METEORITES; CHEMICAL FRACTIONATION; INDUCTIVELY COUPLED PLASMA METHODS; MASS SPECTROSCOPY; LASER METHODS